Adaptive Decentralized Control Scheme for a Stochastic Interconnected System. (29th August 2020) - Jiang, Xiaoli; Liu, Siqi; Liu, Mingyue; Yang, Li; Liu, Lina
Abstract : This work investigates a decentralized state feedback scheme of neural network control for an interconnected system. The completely unknown associated terms are estimated directly by the neural structure. A modified approach is proposed to deal with the state feedback format. By combining the Lyapunov function and backstepping technology together, an adaptive decentralized controller is established, and we can construct the boundedness of all signals in the closed-loop structure through the controller, which can drive the formation of a given reference signal. In the end, the effectiveness of the presented strategy is referred to a simulation example.